Physically real and virtual reality exposed line bisection response patterns: visuospatial attention allocation in virtual reality - Kállai, János; Páll, Tamás; Topa, Kristóf; Zsidó, András Norbert (Frontiers in Psychology, 2023)
To understand the nature of hemispatial attention allocation in virtual reality (VR), a line bisection task (LBT) was administered both in a real environment and a virtual environment to assess the rate of pseudoneglect. The mental construction of real and virtual environments was assumed to increase visuospatial activity in right hemisphere-related cognitive processes; an alteration in the activity that manifests in the direction and rate of line bisection lateral error. In the present study, fifty-one right-handed healthy college students were recruited. They performed a line bisection task in real and virtual environments. The obtained data showed that LBT errors in real and VR environments were correlated and individually consistent. Furthermore, a leftward LBT error was found in the physically real environment, however, in a VR the line bisection bias drifted towards the right hemispace. Participants with a lower right-handedness score showed a lower rate of left LBT bias in a real environment, but in VR, their LBT error showed a stronger rightwards error. Conclusion: Participants showed an individually consistent pattern in both real and VR environments, but VR-induced visuospatial reality construction was associated with rightward LBT bias in a virtual environment.